LEGAL REGULATION OF THE USE OF ARTIFICIAL INTELLIGENCE IN ARBITRATION - Nodirakhon ABDURAKHMANOVA (Scholar Express Journals, 2024)
In today's world, artificial intelligence (AI) is playing an increasingly important role in various fields, including law and arbitration. The emerging opportunities and challenges associated with the use of AI in arbitration processes highlight the need for clear and balanced legal regulation. In this article we will look at the key aspects of such regulation, as well as current trends and prospects in this area.
Keywords: artificial intelligence; arbitration; arbitrability